Conservation research presence protects: a case study of great ape abundance in the Dja region, Cameroon - Tagg, N.; Willie, J.; Duarte, J.; Petre, C.-A.; Fa, J.E. (Wiley, 2015)
Research programmes have been shown to exert a positive impact on faunal communities, but few studies provide empirical evidence. In this study, we surveyed three neighbouring sites, differing in terms of official protection status and level of active management, in the Dja Conservation Complex, southeast Cameroon. We recorded signs of human activity and anthropogenic pressures and found that they significantly differed by site. We assessed chimpanzee and gorilla relative abundance using nest count surveys. We found that chimpanzee nest abundance was related to the presence of active management, but both active management and availability of suitable habitat affected gorilla nest abundance. Our results suggest that gorillas are more tolerant of human activity. We also provide evidence that the presence and activities of the conservation research project Projet Grands Singes served to actively deter poachers and limit hunting of great apes as a result of researcher presence, community sensitization and of valuing living apes and intact forests by local people. Such empirical evidence for the positive effect of research activity on biodiversity preservation should encourage continued investment in such programmes as part of a landscape‐wide, multi‐stakeholder conservation management of great ape habitats.